2021
DOI: 10.1016/j.eclinm.2021.101013
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of asymptomatic or mild SARS-CoV-2 infection on female fertility and in vitro fertilization outcomes: A retrospective cohort study

Abstract: Background: The current study aimed to investigate the impact of asymptomatic or mild severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection on female fertility and laboratory and clinical outcomes in assisted reproductive technology (ART) treatments. Methods: Patients undergoing ART treatments in the Reproductive Medicine Center, Tongji Hospital, Wuhan, from May 2020 to February 2021 were enrolled. Seventy of them were positive for serum SARS-CoV-2 antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 44 publications
(48 reference statements)
5
55
1
5
Order By: Relevance
“…The levels of FSH and AMH were measured during day 2 or 3 of menstruation and AFC was calculated by transvaginal ultrasound. They observed no differences between women with IgG for SARS-CoV-2 and the control group [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The levels of FSH and AMH were measured during day 2 or 3 of menstruation and AFC was calculated by transvaginal ultrasound. They observed no differences between women with IgG for SARS-CoV-2 and the control group [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…They compared the number of the retrieved oocytes, the mature oocyte rate, the fertilization rate, and the blastocyst formation rate, but only the latter was significantly lower ( p = 0.02). There was no difference between results in the biochemical pregnancy rate, early miscarriage rate, and clinical pregnancy rate [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…found that SARS-CoV-2 infection in females might not negatively affect female fertility and embryo development by analysing assisted reproductive technology (ART) data (Ref. 107 ). The study compared the embryo outcomes of females with and without a history of SARS-CoV-2 infection via propensity score matching and found that the ovarian reserves and ovarian responses between groups were similar, as were the proportions of mature oocytes, fertilised oocytes, high-quality embryos and available blastocysts.…”
Section: Impacts Of Covid-19 On the Female Reproductive Systemmentioning
confidence: 99%